1965
DOI: 10.1037/h0022110
|View full text |Cite
|
Sign up to set email alerts
|

Convergent and divergent thinking abilities of talented adolescents.

Abstract: A standard intelligence test (CTMM) used as a measure of convergent thinking (CT), and a composite measure of divergent thinking ability (DT) were the independent variables for a series of 2factorialjinalyses of variance, based on 192 talented junior high-school pupils (X for CTMM = 124). High DT Ss scored higher on tests of word fluency, reading ability, and Holtzman Inkblot Technique scores for movement, anxiety, hostility, color, penetration, and use of large areas of the blots. On a biographical form, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

1968
1968
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 9 publications
3
10
0
Order By: Relevance
“…Clark, Veldman, and Thorpe (1965) reported a creativity-intelligence dichotomy consistent with the earlier work of Getzels and Jackson (1962), although Marsh (1964) had contradicted the Getzels-Jackson position with his analyses and had concluded that the conventional IQ remained the best single criterion for creative potential.…”
Section: The Creativity Researchsupporting
confidence: 61%
“…Clark, Veldman, and Thorpe (1965) reported a creativity-intelligence dichotomy consistent with the earlier work of Getzels and Jackson (1962), although Marsh (1964) had contradicted the Getzels-Jackson position with his analyses and had concluded that the conventional IQ remained the best single criterion for creative potential.…”
Section: The Creativity Researchsupporting
confidence: 61%
“…Standard administration procedures were followed with all subjects, with almost verbatim records of responses obtained All HIT protocols were scored and check-scored by highly tramed scorers on the 22 standard scormg vanables Reaction Tune (RT), Rejection (1961) Previous studies of the total scores on each of tihese 22 vanables, obtamed by summmg the mdividual response scores across the 45 cards, have mdicated that uniformly high test-retest, mterscorer, and spht-half rehabihties have been achieved for the majonty of these vanables (Holtzman, et al, 1961) On the basis of the factonal structure of HIT scores (Holtzman, et al, 1961), as well as previous studies with the technique usmg external cntena (eg, Moseley, Duffey, & Sherman, 1963, Clark, Veldman, & Thorpe, 1965, Fisher, 1963, predictions were made regarding group differences on 20 of the 22 standardized HIT scores Given the nature of the task presented by the HIT and the artist's charactenstic active and personal participation m creative production and m structurmg his perceptual world, subjects m this group were hypothesized to differ from the Engmeer group as follows higher scores on C, Sh, M, V, H, At, Sx, Ab, Ax, Hs, and Pn…”
Section: Subjectsmentioning
confidence: 96%
“…Clark, Veldman, and Thorpe (1965) found that the creative adolescent was more mature (stable) and less constricted than other adolescents, while Kurtzman (1967) concluded that creative individuals are better able to tolerate stimulus ambiguity and are more mature. Cashdan & Welsh (1966) found creative youths to be more independent, more adaptive, and better able to deal with ambiguity.…”
mentioning
confidence: 97%